LOI and TCE Language of Instruction and Attainment of Transnational Coaching Education - Tiboroha, Jonas Benedict (Journal of Sport Coaching and Physical Education, 2023)
This paper provides an in-depth examination of how the LOI as a learning capital and resource was a barrier among Tanzanian football coaches to attain coaching knowledge and skills through transnational coach education programmes (TCEPs). Bourdieu’s notion of “forms of capital” was a theoretical lens used to understand how the use of foreign language for instruction was a barrier for course participants to attain coaching knowledge and skills during the CAF B License course. Using a hermeneutic phenomenological approach, data were collected using interviews and meaning and lived experiences among course participants were analyzed using content analysis. Results establish that the language was a key barrier to learning and caused by educational backgrounds of the course participants. Lack linguistics proficiency compromised their ability to communication and integrate learned experiences, transfer learned content and opted to direct learning intentions as an option to gain credits for accreditation. This paper recommends focused attention to local cultural contexts to benefit the course participants who are recipients of TCEPs. In addition, the paper recommends a learner-centred approach in which the translation of program materials and specific support mechanisms are adopted.